Analisis Motivasi Terhadap Kinerja Kader Posyandu Berdasarkan Teori Victor Vroom - Yeni Rahmah Husniyawati; Ratna Dwi Wulandari (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2016)
The coverage of under-five children weighed at Posyandu represent the level of participation mothers in Posyandu activities. During three-year period, the coverage of under-five children weighed at Posyandu Puskesmas Sidotopo Wetan Surabaya City has not reached the target. It is also the responsibility of cadres. The object of this study was to to analyze the effect of motivation on the performance of health cadres based on Victor Vroom expectancy theory motivation in Posyandu Puskesmas Sidotopo Wetan Kota Surabaya. This research was an analytic observational research with quantitative approach. Design was cross sectional. Sampling was done by using simple random sampling method. The results showed that the performance varied health cadres that was lacking, enough and good. Level of health cadres motivation was high. Health cadres had high score of expectancy, instrumentally, and valency.Ordinallogistic regression analys was showed the influence of motivation (p-value = 0.000) on the performance of cadres (p-value <α (0.05)). In conclusion, motivation influenced the performance of health cadres in Posyandu Puskesmas Sidotopo Wetan Surabaya City.Keywords:motivation, performance, health cadres, posyandu, victor vroom